Pengaruh Dukungan Keluarga, Teman Sebaya, dan Motivasi Diri terhadap Niat Mahasiswa Agribisnis Bekerja di Sektor Pertanian (Jurnal Riset Agribisnis dan Peternakan, 2026)
The low interest among the younger generation in working in the agricultural sector in recent years has impacted the future regeneration of Indonesian agriculture. This study analyzes the influence of family support, peer support, and self-motivation on agribusiness students’ intention to work in the agricultural sector. Family and peer support are external factors that influence future career decisions, while self-motivation is an internal factor in determining one’s career choice. The research method employed a descriptive quantitative approach with a sample of 169 agribusiness students from Satya Terra Bhinneka University selected through purposive sampling. Data were collected via an online questionnaire and analyzed using SEM-PLS with the assistance of SmartPLS 3.0 software. The results indicate that family support, peer support, and self-motivation significantly influence agribusiness students’ intention to work in the agricultural sector, with motivation contributing the most. These findings emphasize the importance of encouraging the younger generation to pursue careers in the agricultural sector. This study provides insights for the development of career guidance programs and strategies to increase students’ interest in working in the agricultural sector in the future